Urban tourism : attracting visitors to large cities - Law, Christopher Michael (London : Mansell, 1993)
This book is about: The urban context; The strategy of urban tourism; Conferences and exhibitions; Urban attractions; ...
Keywords: Tourism; Cities; Towns; Tourism; Cities and towns; Tourism and city planning